SOLUTION FOCUS BRIEF COUNSELING DALAM PERSPEKTIF AL-QUR’AN SEBAGAI MANIFESTASI PENDIDIKAN MASA KINI - Masril Masril; Yaumil Afiat (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2020)
The writers  describes the concept of SFBC (Solution Focused Brief Counseling) throught Al-Qur'an perspective. This approach is grounded on the positive assumption that people are healty and competent. People have the ability to construct solutions that enhance their lives.   This study uses literature studies, by collecting data and information about SFBC. The result of the studi  explain that the concept of SFBC was supported by education carried out. The education will be construct the mindset of the people to make a changes in their lives. SFBC its essence lies in the counseling phase focused on solutions to solve their problem. If the people can believed their capability to solve their problem, so that will be posible. Allah will be  give a problem to the people according by capability the people.Keywords: solution focus brief counseling, education, Al- Qur’an perspective